Coastal tourism space in the context of climate change: discourses and strategies. (10th October 2016) - Lapointe, Dominic; Lebon, Coralie; Guillemard, Alexis
Abstract : Purpose: The purpose of the paper is to explore how climate change and the discourses about adaptation to climate change are altering the spatial development of the tourism industry in coastal destinations. The paper also identifies how tourist development and climate change adaptation can be combined to transform space and place, especially in coastal tourism areas. Design/methodology/approach: Using a theoretical approach based on the concept of production of space, the study focuses on relational space, relationships expressed through representations of space and social practices. A case study method is used to analyze the socio-geographic processes at work in the adaptation to climate change in a coastal tourism community in Quebec, Canada. The analysis of the study utilized Nvivo with thematic textual queries. Findings: The results reveal an adaptation process at work, based on a "hold the line" strategy, where private stakeholders choose to invest in defensive structures to mitigate the impact of rising sea levels and erosion. This strategy reflects coordinated action in the face of the risk and to protect high-value land property. Research limitations/implications: This research illustrates how tourism and climate change adaptation discourses intersect. It also reveals how tourism development promotes the values and image of coastal space and how this can conflict with an efficient climate change adaptation strategy. Originality/value: This research provides guidelines for coastal tourism communities, enabling them to design their own climate change adaptation strategy, taking into account how the different social discourses and tourism practices interact with climate change adaptation. It also provides some insights into the criteria that influence an effective climate change adaptation strategy.